The Effectiveness of 5% Tea Tree Oil cream, 10% Tea Tree Oil cream, and 5% Permethrin Cream for Scabies Treatment in Pediatric Patients - Chesia Christiani Liuwan; Muhammad Yulianto Listiawan; Dwi Murtiastutik; Evy Ervianti; Sawitri Sawitri; Cita Rosita Sigit Prakoeswa; Linda Astari; Farhat Surya Ningrat; Kurniati Kurniati; Endang Wahyu Fitriani; Irmadita Citrashanty; Regitta Indira Agusni; Iskandar Zulkarnain (Faculty of Medicine, Universitas Airlangga, 2020)
Background: Scabies, an infectious disease caused by Sarcoptes scabiei mites, is still one of the most common skin diseases found in developing countries, including Indonesia. The 5% permethrin cream for scabies treatment has been investigated as having 2–3 time to cure scabies. Tea Tree Oil (TTO) is one of the agents that has been proven to have acaricidal potential as an anti-inflammatory, antibacterial, and antipruritic agent. It has minimal side effects in topical use. Purpose: To evaluate the effectiveness of 5% TTO cream and 10% TTO cream in scabies treatment of pediatric patients. Methods: This was an experimental, analytical study with controlled clinical trial methods, and a double-blind, parallel design comparing 5% TTO cream (treatment 1), 10% TTO cream (treatment 2), with 5% permethrin cream (control) to children with scabies. Result: The 5% TTO cream gave a cure rate of 61.5% and was significantly different from the 5% permethrin cream groups with a p-value = 0.044 in the first week of the study. The 5% permethrin cream gave a cure rate of 15.4%, and the cure rate of 10% TTO cream was 53.8% in the first week of the study. Conclusion: There was a significant difference between the 5% TTO cream and 5% permethrin cream in the first week of the study. The highest and fastest cure rates were found in the 5% TTO cream treatment group.